Human Immunodeficiency Virus (HIV) Incidence in Cilacap Regency 2020–2024 - Frisca Dewi Yunadi; Bambang Budi Raharjo; Yogi Andhi Lestari; Sohimah Sohimah (Jurnal Kebidanan, 2026)
Human Immunodeficiency Virus (HIV) remains a significant public health problem in Indonesia, including in non-metropolitan areas such as Cilacap Regency. This study aims to describe the incidence of HIV in Cilacap Regency based on surveillance data from 2020–2024. This study used a descriptive observational design with a secondary data analysis approach. Data were sourced from the recapitulation of HIV reports from the Cilacap Regency Health Office for 2020–2024, with the study population comprising all HIV cases recorded during that period. Data analysis was conducted using univariate methods and presented in the form of frequency distributions and descriptive narratives. The results show that HIV cases are consistently detected annually, with a trend of increasing cases in recent years. The majority of cases occur in men. Most people with HIV/AIDS have received antiretroviral therapy (ARVs), although there are still cases of HIV-related deaths and individuals who have not or are not recorded as receiving ARVs. Based on population groups, HIV cases were most frequently found among men who have sex with men (MSM), followed by the general population and partners of people living with HIV/AIDS. These findings indicate that the HIV epidemic in Cilacap Regency is concentrated in key groups, but has spread to the general population. The conclusion of this study confirms that the HIV incidence in Cilacap Regency is ongoing and requires strengthening prevention efforts, early detection, and treatment continuity based on local data and a comprehensive approach.